Pengaruh Schroth Exercise Terhadap Peningkatan Fungsional pada Anak Penderita Skoliosis: Studi Kasus - Fahreza Fatih Izzulhaq; Wahyuni Wahyuni; Atih Hidayati (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction: Scoliosis is the most common deformity of the spine. Scoliosis is defined as a lateral curvature of the spine that is 100 degrees or greater. (Hresko, 2013). Adolescent idiopathic scoliosis is a structural deformity of the spine with 3-dimensional deformation, including lateral shift and rotation of the vertebrae that affects children at puberty. In the general population, the prevalence of AIS is approximately 2.5% with a Cobb angle >10 degrees. Various risk factors can lead to the development of a higher curve, including female sex, age 10-12 years, absence of menarche, presence of a thoracic curve, curve size at presentation >25 degrees. Objective: to determine the effect of providing intervention in the form of Schroth Exercise and Infra Red in improving function with the SRS 22r Patient Questionnaire in children with scoliosis. Research Methods: This study used single-subject research with the ABA design approach. Performed directly on 1 pediatric patient with scoliosis with therapy given 4 times for 4 weeks. The results obtained after 4 therapy sessions showed that there was a functional increase, a decrease in the degree of pain, an improvement in self-image, an increase in mental health and an increase in satisfaction with therapeutic measures. Conclusion: it can be said that Schroth Exercise in children with scoliosis has been shown to be able to have a positive impact on improving function by using the SRS 22r Patient Questionnaire assessment.Keywords: Skoliosis, Schroth Exercise, Fungsional, SRS 22r Patient Questionnaire